La carte DSP TMS320 C6713 DSK pour la conception des filtres numériques - Abdi Hadjer; Ben ghechoua Asma; Reguiegue Mourad (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DEPARTEMENT D’ELECTRONIQUE, 2022)
The DSP is a processor specialized in digital signal processing. Its architecture is optimized to process a large amount of data in parallel at each clock cycle. This operating mode is very effective in the processing of digital signals (filtering, compression, extraction, etc.) such as video or music. DSPs are used in most real-time digital signal processing applications. This graduation project aims to study the design of digital filters by DSP TMS320C6713 as well as the evaluation board TMS320C6713DSK for digital filters, so that we can study this filter in a practical way.
Option : Réseaux et télécommunications